Bacteroides fragilis strain ZY-312 facilitates colonic mucosa regeneration in colitis via motivating STAT3 signaling pathway induced by IL-22 from ILC3 secretion - Zhang, Wendi; Zhou, Qian; Liu, Hongbin; Xu, Jiahui; Huang, Ruo; Shen, Binhai; Guo, Yandong; Ai, Xiuyun; Xu, Jun; Zhao, Xinmei; Liu, Yangyang; Wang, Ye; et al. (Frontiers in Immunology, 2023)
Probiotics play critical roles in relieving inflammatory bowel disease (IBD). However, the underlying mechanism of Bacteroides fragilis strain ZY-312 (B. fragilis) for colonic mucosa regeneration in IBD remains unclear. Here, we showed that B. fragilis motivated STAT3 phosphorylation in colonic mucosa with the upregulation of proliferation index Ki-67 and mucus density, the downregulation of apoptosis level, and the modulation of gut microbiota, suggesting that B. fragilis promoted colonic mucosa regeneration through the STAT3 signaling pathway. To investigate the role of STAT3 in colitis development, Stat3△IEC mice and wild type (Stat3fl/fl) littermate controls were treated with B. fragilis in Dextran Sulfate Sodium Salt (DSS)-induced colitis. We found that Stat3△IEC mice exhibited severe colon inflammation, lower expression of Ki-67 and mucus density than Stat3fl/fl controls do. Furthermore, our results indicated that B. fragilis promoted IL-22 production, and increased the percentage of IL-22-secreting type 3 innate lymphocytes (ILC3) in colitis. And we verified that IL-22-/- mice with B. fragilis administration in colitis exhibited little expression of STAT3 phosphorylation (pSTAT3) with severe colon inflammation, lower expression of Ki-67 and mucus density than wild type (IL-22+/+) do. In summary, we show that B. fragilis facilitates colonic mucosa regeneration via motivating STAT3 signaling pathway induced by IL-22 from ILC3 secretion.